Effectiveness of low cost adapted school furniture on the functional performance of a child with cerebral palsy - Marco Aurélio Teixeira Piovezanni; Aila Narane Dahwache Criado Rocha; Lígia Maria Presumido Braccialli (Universidade Federal de Santa Maria (UFSM), 2014)
Individuals with cerebral palsy present an atypical motor function, characteristic altered postures in movement coordination and muscle tone. This causes limitations in their ability to perform functional activities. In this context, the introduction of assistive technology is vital to the objective of augmenting their ability to function productively and be included in society. It is common for individuals with cerebral palsy to have difficulty maintaining body dynamics, especially with seated posture. The objective of this study is to produce an adapted school desk and adapted school chair with low cost materials and to study their efficacy in adjusting the writing motor skills of a child with cerebral palsy. This stydi's case is a boy who has been diagnosed with diplegic cerebral palsy. The collection and registration of data was done in three stages, with the child positioned in adapted furniture, regular school furniture and again in the furniture adapted to establish a comparison. Data analysis was through nonparametrical statistical tests. There was no statistical significance and was verified inconsistency in the data presented, because cannot be said for sure wich furniture was more effective in carrying while performing a proposed task and even if there was learning motor with its repetition. This fact does not invalidate the adequacy of school furniture to the student with cerebral palsy, because is an important factor facilitate control and postural stability to the individual, which interferes with fine motor skills of these individuals, influencing their performance in school activities.